Combined analysis of electrical and electromagnetic methods with geotechnical soundings and soil characterization as applied to a landslide study in Campos do Jordão City, Brazil - Bortolozo, Cassiano Antonio; Motta, Mariana Ferreira Benessiuti; Andrade, Marcio Roberto Magalhães de; Lavalle, Laura Vanessa Araque; Mendes, Rodolfo Moreda; Simões, Silvio Jorge Coelho [UNESP]; Mendes, Tatiana Sussel Gonçalves [UNESP]; Pampuch, Luana Albertani [UNESP] (My University, 2019)
Every year, especially in summer, Brazil suffers from floods and landslides triggered by intense rainfall. These landslides are responsible for many fatalities and material losses that greatly affect the local population. The municipality of Campos do Jordão, in São Paulo state, presents such a history of mass movements that have resulted in fatalities and financial losses. A map of the municipality's risk assessment shows that about 32% of the municipality's population lives in risky areas. For this reason, Campos do Jordão is currently one of the pilot areas being used in studies for understanding landslides and mitigation techniques. In this context, this paper presents the results of an integration of geophysical surveys of, and geotechnical information on, the area. The geophysical methods applied were electrical resistivity, induced polarization, and frequency-domain electromagnetics. The geotechnical data included standard penetration test soundings and soil characterization (using particle density and X-ray fluorescence methods). The main contribution of this work is to present results from the joint application of these methodologies. Results from one of the critical areas, where a school had suffered the impact of a mass movement, indicated the displacement and burial of the retaining wall, which was built in 2002, as well as the shape of the movement, which affected the foundations of the school. It was also possible to determine the critical geological structures involved in the slope dislocation, and the potential problems with the school's foundations. The combined application of geophysical and geotechnical methods to landslide research is not very common, and so this study aimed to provide a field-based example to demonstrate the potential utility of such an integrated approach. The aim was also to foster collaboration with studies of mass movements in Brazil and help create methodologies for investigating and understanding the phenomenon.
Keywords: Campos do Jordão, São Paulo State – Brazil; Electrical method; Electromagnetic method; Geotechnical surveys; Mass movements; Soil characterization